Osborn Waves in a Severely Hypothermic Patient - James Elliot Karz, DO; Grant Wei, MD; Chirag Shah, MD (Journal of Education and Teaching in Emergency Medicine, 2018)
History of present illness: An 88-year-old female was found lying prone and unresponsive outside of her home with an unknown downtime. She was intubated in the field by medics and brought to the emergency department (ED). In the ED, she had a core temperature of 78 degrees Fahrenheit (°F) with a heart rate of 21 beats per minute. Active rewarming and resuscitation were started and serial electrocardiograms (ECGs) were performed; two hours later, her core temperature had increased to 86°F.